1985
DOI: 10.1111/j.1365-2672.1985.tb01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinone composition of mycolic acid‐containing actinomycetes and some sporoactinomycetes

Abstract: The menaquinones of 141 actinomycetes representing the genera Caseobacter, Mycobacterium, Nocardia, Rhodococcus and some related taxa lacking mycolic acids were examined by mass spectrometry. The mycolic acid-containing strains were assigned to four groups on the basis of the predominant isoprenologue detected: Rhodococcus coprophilus, R. equi, R. erythropolis, R. globerulus, R. rhodnii, R. rhodochrous and R. ruber contained dihydrogenated menaquinones with eight isoprene units; Nocardia asteroides, N. brasili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…thesis) and therefore is designated the type strain of Amycolata alni. Three other strains (strains VKM Ac-759, VKM Ac-1066, and VKM Ac-813 [a variant of strain VKM Ac-10661) have been stored in culture collections for a long time, and strain VKM Ac-1066 (= NCIB 8939) is rather well studied (5,14,15,24). Below is a description of the new species.…”
Section: Discussionmentioning
confidence: 99%
“…thesis) and therefore is designated the type strain of Amycolata alni. Three other strains (strains VKM Ac-759, VKM Ac-1066, and VKM Ac-813 [a variant of strain VKM Ac-10661) have been stored in culture collections for a long time, and strain VKM Ac-1066 (= NCIB 8939) is rather well studied (5,14,15,24). Below is a description of the new species.…”
Section: Discussionmentioning
confidence: 99%
“…McNEIL AND BROWN (Table 1). Currently, the chemotaxonomic criteria used to assign bacteria to the genus Nocardia include the presence of the meso isomer of 2,6-diaminopimelic acid (DAP) and whole-cell sugars, arabinose and galactose (cell wall type IV) (331); intermediate-chain mycolic acids (46 to 60 carbons) (11,88,89,201,203,335); a fatty acid profile showing major amounts of straight-chain, unsaturated, and tuberculostearic acids (336); and the presence of a menaquinone fraction containing a tetrahydrogenated menaquinone with eight isoprene units as the predominant isoprenoic quinone (119,649,650). Tests that have established the heterogeneity of N. asteroides include numerical taxonomy (48,394,431,600), mycolic acid analysis by gas chromatography (651), DNA relatedness (651), and antimicrobial resistance patterns (625).…”
Section: Nocardia Speciesmentioning
confidence: 99%
“…The remaining Rhodococcus spp. contain shorter-chain mycolic acids (C34 to C52) and a dihydrogenated menaquinone with eight isoprene units as the major isoprenoic quinone (119,239). Of interest, it was recently shown that Rhodococcus chubuensis, listed as a species incertae sedis in Bergey's Manual ofSystematic Bacteriology (198), contains a mycolic acid pattern similar to that of G. bronchialis (134).…”
Section: Pathogenicity Studiesmentioning
confidence: 99%
“…This can be used as a classifying marker (8). The menaquinone compositions of Nocardia species (except Nocardia amarae) (21) are different from the menaquinone compositions of Corynebacterium, Rhodococcus, and Mycobacterium (4, 7,10,11,43).…”
mentioning
confidence: 93%
“…This can be used as a classifying marker (8). The menaquinone compositions of Nocardia species (except Nocardia amarae) (21) are different from the menaquinone compositions of Corynebacterium, Rhodococcus, and Mycobacterium (4, 7,10,11,43).Rhodococci undergo rod-to-coccus variation during the growth cycle (23,27). This kind of morphological variation does not occur in the true corynebacteria (23, 27).…”
mentioning
confidence: 99%